The language of leaving: Brexit, the second world war and cultural trauma. Issue 3 (3rd July 2019) - Stratton, Jon
ABSTRACT: This article considers the language use in the Brexit debate, especially by the leading figures who argued for Leave. I argue that historically those who identify as English have had anxieties focused around invasion, occupation and loss of sovereignty. In 1940 these fears materialised in the possibility of invasion by Hitler's forces. The unresolved cultural trauma associated with these fears has meant that discussions about the United Kingdom's presence in the European Union have tended to framed in language referring to World War 2 where the European Union's impact on the United Kingdom is rhetorically constructed in the emotive terms of Nazi invasion, occupation and loss of sovereignty.